2012
DOI: 10.1155/2012/191789
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Health Behaviour Change in an E-Counseling Intervention for Hypertension

Abstract: We evaluated the influence of psychological stress and depression on motivation to adhere to recommended guidelines for exercise and diet. This study was conducted within a larger e-counseling trial. Subjects diagnosed with hypertension (n = 387, age = 44–74 years, 59% female) completed assessments at baseline and within 2 weeks after a 4-month intervention period. Outcomes included mean level of readiness to change diet and exercise and symptoms of depression and stress. Per protocol analysis defined e-counse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
0
16
0
2
Order By: Relevance
“…Finally, intervention studies targeting stress [284] or exercise/health behaviors [89, 124, 204, 281, 285-287] have found inverse associations between stress and indicators of PA over time. For instance, Urizar et al [89] found that PA changes over a 10-week period were moderately correlated with maternal stressors over the same period ( r = –0.42).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, intervention studies targeting stress [284] or exercise/health behaviors [89, 124, 204, 281, 285-287] have found inverse associations between stress and indicators of PA over time. For instance, Urizar et al [89] found that PA changes over a 10-week period were moderately correlated with maternal stressors over the same period ( r = –0.42).…”
Section: Resultsmentioning
confidence: 99%
“…Some interventions, however, have found no association [145, 273, 276, 277] or that higher stress relates to greater PA [279]. Improvements in exercise readiness over time are compromised by the experience of stress [124]. Whether stress has a stronger association with adoption or continued participation of an exercise routine/PA programming is undetermined [184, 278, 288].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em uma metanálise, que teve como propósito investigar novas estratégias para que indivíduos portadores de SM modifiquem o seu estilo de vida, os autores observaram que o aconselhamento pelos profissionais de saúde pode aumentar significativamente a motivação em adquirir hábitos saudáveis de vida, incluindo a dieta [38]. Nesse sentido, torna-se importante, também, conhecer os sintomas de estresse psicológico e de depressão, visto que esses aspectos podem influenciar significativamente a adesão para mudar comportamentos [39].…”
Section: Discussionunclassified
“…With the widespread accessibility and uptake of daily internet use and email in today' s society, it is important to consider the potential role of electronic forms of exercise counselling for use in primary care as a mechanism to increase motivation and adherence to physical activity (Durrani, et al, 2012). uptake is essential for patients with depression.…”
Section: Practice Considerations For Primary Carementioning
confidence: 99%